Cryobiopsy increases the EGFR detection rate in non-small cell lung cancer. (March 2020) - Haentschel, Maik; Boeckeler, Michael; Ehab, Ahmed; Wagner, Robert; Spengler, Werner; Steger, Volker; Boesmueller, Hans; Horger, Marius; Lewis, Richard A.; Fend, Falko; Kanz, Lothar; Bonzheim, Irina; et al.
Highlights: "Biopsy techniques influence the detection of moleculargenetic alterations". "Cryobiopsy showed a higher detection rate of EGFR mutations than other techniques". "Cryobiopsy may optimize individualized NSCLC treatment". Abstract: Objectives: Detection of activating epidermal growth factor receptor (EGFR) mutation is crucial for individualized treatment of advanced non-small-cell lung cancer (NSCLC). However little is known about how biopsy technique affects the detection rate of EGFR mutations. This retrospective, single center study evaluated the detection rate of EGFR mutations in tissue obtained by bronchoscopic cryobiopsy and compared this to other standard tissue sampling techniques. Materials and methods: We retrospectively analyzed 414 patients with histologically confirmed NSCLC and known EGFR mutation status between 3/2008-7/2014. Tumor specimens obtained by tissue preserving bronchoscopic cryobiopsy were compared to those obtained by other techniques. Results and conclusion: Analysis of bronchoscopic cryobiopsy tissue detected 29 activating EGFR mutations in 27 (21.6 %) out of 125 patients, while analysis of tissue obtained by non-cryobiopsy techniques (bronchoscopic forceps biopsies, fine needle aspiration, imaging guided transthoracical and surgical procedures) detected 42 EGFR mutations in 40 (13.8 %) out of 298 patients (p < 0.05). Cryobiopsy increased detection rate of EGFR mutations in central tumors compared with forceps biopsy (19.6 % versus 6.5 %, p < 0.05), while an insignificant trend was detected also for peripheral tumors (33.3 % versus 26.9 %). Bronchosopic cryobiopsy increases the detection rate of activating EGFR mutations in NSCLC in comparison to other tissue sampling techniques. This will help to optimize individualized treatment of patients with advanced tumors. Because of the retrospective nature of this analysis, a prospective trial is mandatory for final assessment.